3D Exfoliated Carbon Paper toward Highly Loaded Aqueous Energy Storage Applications. Issue 11 (18th September 2019) - Song, Yu; Duan, Sicong; Yang, Duo; Dong, Ran; Guo, Di; Sun, Xiaoqi; Liu, Xiao-Xia
Abstract : Commercial electrodes need high mass loadings to realize superior energy and power densities. However, good electrochemical properties are usually achieved in the electrodes with ultrathin active materials (e.g., <1 mg cm −2 ). Good performance and high mass loading are often mutually exclusive characteristics. Herein, a unique 3D exfoliated carbon paper (EC) is demonstrated using a facile electrochemical method to support high mass loading MnO2 materials. The 3D‐interconnected graphene/graphite network, highly porous structure, as well as the strong interaction between the active materials and the substrate, allow efficient charge transport in the composite electrode, addressing the traditional limitations in high mass loading electrodes. The deposited MnO2 (mass loading: 9.5–10 mg cm −2 ) achieves a remarkable capacitive performance with high areal and gravimetric capacitances of 5.1 F cm −2 and 537 F g −1, respectively. A Zn–MnO2 battery is also assembled using MnO2 /EC as the cathode. An excellent specific capacity of 368 mAh g −1 is also delivered. This MnO2 /EC outperforms most of the reported MnO2 ‐based electrodes with similar loadings for capacitive and Zn‐ion battery applications, highlighting the great application potential of the 3D carbon paper support in electrochemical energy storage. Abstract : A 3D carbon paper support is demonstrated using a facile electrochemical exfoliation method. High mass loading MnO2 materials deposited on this carbon support exhibit remarkable electrochemical performance, highlighting the great application potential of the 3D carbon paper support in electrochemical energy storage.